A new pathogenic isolate of Kocuria kristinae identified for the first time in the marine fish Larimichthys crocea - Meng, Xiangyu; Chen, Fangyi; Xiong, Ming; Hao, Hua; Wang, Ke-Jian (Frontiers in Microbiology, 2023)
In recent years, new emerging pathogenic microorganisms have frequently appeared in animals, including marine fish, possibly due to the climate change, anthropogenic activities and even cross-species transmission of pathogenic microorganisms among animals or between animals and humans, which brings a large risk for preventive medicine. In this study, a bacterium was clearly characterized among 64 isolates from the gills of diseased large yellow croaker Larimichthys crocea that were raised in marine aquaculture. This strain was identified as K. kristinae by biochemical tests with VITEK 2.0 analysis system and 16S rRNA sequencing and named K. kristinae_LC. The potential genes that might encode virulence-factors were widely screened through sequence analysis of the whole genome of K. kristinae_LC, and many genes involved in the two-component system and drug-resistance were also annotated. In addition, 104 unique genes in K. kristinae¬_LC were identified by pan genome analysis with the genomes of this strain from five different origins (woodpecker, medical resource, environment and marine sponge reef) and the analysis results demonstrated that their predicted functions might be associated with adaptation to living conditions such as higher salinity, complex marine biomes and low temperature. A significant difference in genomic organization was found among the K. kristinae strains that might be related to their hosts living in different environments. The animal regression test for this new bacterial isolate was carried out using L. crocea, and the results showed that this bacterium could cause the death of L. crocea and that the fish mortality was dose-dependent within five days post infection, indicating the pathogenicity of K. kristinae_LC to marine fish. Since K. kristinae has been reported as a pathogen for humans and bovines, in our study, we revealed a new isolate of K. kristinae_LC from marine fish for the first time, suggesting the potentiality of cross-species transmission among animals or from marine animals to humans, from which we would gain insight to help in future public prevention strategies for new emerging pathogens.